Lesotho Social Accounting Matrix, 2007 - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The Lesotho Social Accounting Matrix (SAM), 2007 is constructed using data that available during the second half of 2011. The SAM provides a detailed representation of the Lesotho economy. It separates 24 activities and 23 commodities; labor is disaggregated by 3 broad skill groups (high, medium and low); and households into 6 groups based on the rural/urban and income earning status of the household head. The SAM is a useful database for conducting economy-wide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.